Seismic Constraints on the Trompsburg Layered Igneous Intrusion Complex in South Africa Using Two Deep Reflection Seismic Profiles - Westgate, Michael; Manzi, Musa S. D.; James, Ian; Andreoli, Marco A. G.; Durrheim, Raymond J. (Frontiers in Earth Science, 2022)
The discovery and characterization of layered intrusions around the globe have been predicated to a large degree on the imaging capabilities of the reflection seismic method. The ability of this tool to detect mineralization zones and structural controls such as faults and folds has been critical in unlocking the economic potential of igneous complexes, most notably the Bushveld Complex in South Africa. In this study, we present novel seismic constraints on the lesser-known Trompsburg Complex in South Africa. Two yet-unpublished seismic profiles were conducted end-to-end in the early 1990s, with a southwest-to-northeast trend through the centre of the ∼2,400 km2 Trompsberg potential field anomaly in South Africa, attributed to a 1915 ± 6 Ma buried layered intrusion complex. The complex was first detected by magnetic and gravity measurements near the town of Trompsburg in 1939 and was subsequently confirmed as a layered intrusion by borehole cores drilled thereafter. The combined length of the two profiles is 108 km. Both profiles have been reprocessed and interpreted to further constrain the subsurface expanse of the Trompsberg Complex along the seismic traverse. Processing and interpretation of the seismic profiles were aided by a handful of studies found in the literature: stratigraphy and physical property measurements of borehole cores that were drilled into the complex in the 1940s; pre-Karoo (∼317 Ma) lithological maps that were constructed based on boreholes in and around the investigation area; and potential field maps of the intrusion area near the town of Trompsburg. Most of the seismic reflection energy is concentrated within the top 1 km in both profiles, where localized reflectors with strong amplitudes are observed, due likely to the dolerite sills that permeate the Karoo cover. These sills obstruct seismic illumination of underlying structures due to their high acoustic impedance contrast with the surrounding soft rock sediments, rendering underlying reflections challenging to identify and enhance. The base of the Karoo is confidently identified to be at an average depth of 1.5 km and several reflection packages have been identified thereunder. These are linked to Proterozoic supracrustals associated with the Witwatersrand, Ventersdorp, Transvaal/Griqualand West, and Kheis Supergroups, as well as the Trompsburg Complex that intruded into them. The geometry of the Trompsburg Complex along the seismic traverse has been constrained with a moderate degree of confidence. It comprises a series of 30° northeasterly dipping reflectors near its southwestern boundary, flat reflectors near its centre at the town of Trompsburg, and 45° southwesterly dipping reflectors near its northeastern boundary. The lateral sub-Karoo extent of the complex is 60 km and its total thickness is difficult to constrain due to lack of deep reflections, but is likely between 6.6 and 7.5 km. The complex subcrops against the Karoo cover except near the southwestern region, where it is overlaid by Waterberg Group sediments.